Conflicts in Marriage Legal Arrangements Differences in Religion Between Laws Islam and Human Rights - Rofiq, Nur; Mahmudah, Husnatul; Rahmawati, Rahmawati (Literasi Hukum, 2023)
In Indonesia, interfaith marriages are still a problem. This is because it not only involves legal conflict issues but also issues of interpretation, psychology, culture, economics, human rights and other related topics. This article presents a discussion regarding the clash of Indonesian legal rules by exploring scientific sources from various sources. This article views Indonesian jurisprudence as a single pattern, the purpose of this article is to show the complexity and dynamics of Indonesian legal regulations regarding interfaith marriages through Islamic legal regulations and human rights. This study focuses on the legal arguments put forward, the legal conflict position taken on the issue of interfaith marriage.In communities that adhere to the Islamic religion and traditional-conservative attitudes, there is no room for interpretation regarding the laws governing interfaith marriages. Even for them, there are no national regulations regarding interfaith marriages or no established norms. The practice of interfaith marriages in Indonesia is because marriage is not strictly and definitely regulated. Rejection of interfaith marriages is classified as discriminatory because it violates human rights principles. Law Number 1 of 1974 concerning Marriage, especially Article 2 paragraph (1), refers more to the validity of marriage based on religious and belief law. Article 3 paragraph (3) of the 1945 Constitution and Article 28 of the 1945 Constitution have different standards.